Cloud Computing and Big Data : Second International Conference, CloudCom-Asia 2015, Huangshan, China, June 17-19, 2015, Revised Selected Papers - Qiang, Weizhong; Zheng, Xianghan; Hsu, Ching-Hsien.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Second International Conference on Cloud Computing and Big Data, CloudCom-Asia 2015, held in Huangshan, China, in June 2015. The 29 full papers and two keynote speeches were carefully reviewed and selected from 106 submissions. The papers are organized in topical sections on cloud architecture; applications; big data and social network; security and privacy.
Cloud architecture -- Applications -- Big data and social networks; security and privacy.
Keywords: Database management; Computer Communication Networks; Software engineering; Data mining; Computer system performance; Operating systems (Computers).; Database Management; Computer Communication Networks; Software Engineering; Data Mining and Knowledge Discovery; System Performance and Evaluation; Performance and Reliability